Cross-temporal and cross-national comparisons of party left-right positions - McDonald, Michael D. (2007)
We investigate the cross-time and cross-nation comparability of party left-right position measurements by expert surveys and the Comparative Manifesto Project (CMP). While expert surveys show party left-right positions to be mostly static, we find the CMP records systematic party movements for one-third of the parties analyzed. On the issue of cross-national comparability, we find cross-national variation in expert surveys is muted. They contain little more than the variation associated with reputations based on party-family affiliation. The CMP measurements, on the other hand, contain variation attributable to national party-system differences. We conclude with thoughts about why all of this is so and about how one might navigate the expert survey limitations depending on the question one wants to answer about democratic politics and policy making.